Spatial structure of agricultural output in Republic of Ireland - Gillmor, D.A. (Economic & Social Studies, 1977)
Mixed livestock production with some arable cropping is the description often taken as applying to the form of agriculture practised throughout Ireland, with little or no reference to the major regional variations in the emphases placed on different farming enterprises which are such a striking feature of the agricultural scene. The complete agricultural enumeration, taken at intervals of five years, provides comprehensive statistics for detailed study of the spatial patterns of crop areas and livestock numbers. In contrast, data relating to the value of farm output are deficient, so that areal analyses of the type available in many other countries have not been done. It is the purpose of this paper to contribute to such analysis by using the agricultural statistics on a rural district basis in conjunction with county output values estimated by Dr M . Ross and converted to gross margin values. These data are employed to outline concisely spatial characteristics of agricultural output.
Keywords: Agricultural Practices; Ireland